The Role of Corporate Governance, Type of Ownership, and Capital Structure, in the Achievement of Sustainable Development Goals - Surifah; Krismiaji (Journal of Indonesian Economy and Business, 2025)
Introduction/Main Objective: This study presents research that makes a theoretical contribution to the literature on the achievement of sustainable development goals (SDGs), and provides empirical evidence of the role of corporate governance (CG), type of ownership, and capital structure of companies in Indonesia in achieving the SDGs. Background Problem: This research is motivated by the phenomenon that the business sector plays major roles in economic growth, damage to the natural environment—as well as its preservation—well the social life of local and global communities. The active involvement of the business world is needed to support the achievement of the SDGs. This research is important because the president directors and president commissioners (as proxies for CG) are the parties that play the biggest roles in their companies in achieving the SDGs. In addition, owners can pressure directors and commissioners to commit to achieving SDGs. A capital structure that reflects the company's financial flexibility also plays a role in realizing the SDGs. Novelty: This research uses unique proxies for the SDGs and CG variables. The SDGs are proxied using the SDG index, covering 17 SDGs fields, consisting of 101 items.CG is proxied by the competence of president directors and president commissioners. Competence is measured by level of education, work experience, and global insight. In addition, research examining the effect of the four types of ownership and capital structure on the SDGs is still very limited. This research was conducted on all companies listed on the Indonesia Stock Exchange during the period 2017 to 2021. The samples were taken purposively, with certain criteria. The dependent variable is SDGs, while the independent variables are CG, type of ownership, and capital structure. The analysis technique uses multiple linear regression. Findings/results: The research proves that the president commissioner, government, and individual shareholders, as well as leverage have a significant positive effect on SDGs disclosure. Meanwhile, domestic institutional shareholders, capital structure, and company size negatively affect SDG’s disclosure. Conclusion: The results show that the president commissioner, government, and individual shareholders become the key shareholders who significantly affect the company’s SDG disclosure policy. Thus, the results confirm and support the stakeholder theory and stewardship theory.